Molecular analysis and genotype-phenotype correlation in patients with antithrombin deficiency from Southern Italy - Castaldo, Giuseppe; Cerbone, Anna Maria; Guida, Anna; Tandurella, Igor; Ingino, Rosaria; Tufano, Antonella; Ceglia, Carlo; Di Minno, Matteo Nicola Dario; Ruocco, Anna Lilia; Di Minno, Giovanni (Thrombosis and Haemostasis, 2012)
We sequenced the SERPINC1 gene in 26 patients (11 males) with antithrombin (AT) deficiency (22 type I, 4 type II), belonging to 18 unrelated families from Southern Italy. Heterozygous mutations were identified in 15/18 (83.3%) families. Of them, eight were novel mutations, each being identified in one family. Seven clearly cause impaired protein synthesis (four frameshift, one non-stop, one splicing and one 21bp deletion). One, present in a single patient, is a missense mutation thought to be causative because: a) it is absent in 100 chromosomes from controls; b) it involves a highly conserved amino acid, whose change is predicted to impair AT activity; c) no other mutation is present in the propositus. Severe mutations (i.e. nonsense, frameshift, deletions) were invariably identified in type I patients. In type II patients, 3/4 were missense mutations; the fourth leads to a 19 nucleotides shift in the stop codon. In addition to the type of mutation, the co-existence of other predisposing factors in most patients helps explain the severity of the present type I cases (age at first event, recurrence during prophylaxis). In the five families in which there was more than one member affected, the same genotype and a concordant clinical expression of the disease were found. We conclude that the molecular bases of AT deficiency in Southern Italy are different as compared to other geographic areas, and that molecular analysis and the study of the effect of the mutation may help predict the clinical expression of the disease.
Keywords: Antithrombin; serpins; highly conserved residues; mutations; thrombosis